Incidence of antibiotics resistance among uropathogens in Omani children presenting with a single episode of urinary tract infection - Sharef W. Sharef; Mohamed El-Naggari; Dana Al-Nabhani; Ali Al Sawai; Zakaria Al Muharrmi; Ibtisam Elnour (Journal of Infection and Public Health, 2015)
Summary: Urinary tract infection (UTI) is one of the most common community-acquired infections. Different organisms can be the cause of UTI in children, with resistance to antibiotics becoming a significant problem in the choice of treatment. Worldwide studies have documented the prevalence of uropathogens in different countries. However, there is no previous study documenting the incidence of different uropathogens in Oman. We aim to report the most common uropathogens and their antibiotic sensitivity patterns in children presenting with documented, single episode UTI at a tertiary hospital in Oman. A retrospective analysis of all Omani children below 14 years who presented with a case of first documented UTI to SQUH between September 2008 and August 2012 was conducted. Data were obtained from the patients’ electronic records in the hospital information system. Data were then analyzed using SSPS (Statistical Package for Social Sciences program, Version 20, IBM, Chicago, IL, USA). In the retrospective review of all urine cultures, 438 positive urine cultures were identified. Out of those, 208 (47.5%) belonged to children with their first episode of UTI. Thirty-three patients were excluded and 75 patients were included in the final analysis. Escherichia coli was the most frequently encountered uropathogen in our cohort (69%), followed by Klebsiella pneumoniae infection (17%). Nearly half (46.6%) of these two common organism were resistant to Cotrimoxazole, while 31% of them were resistant to Augmentin. Twenty-four percent of the E. coli and K. pneumoniae strains were resistant to Cefuroxime, and only 10% were resistant to nitrofurantoin. Both Augmentin and Cotrimoxazole should not be the first line antibiotics to treat UTI. Keywords: Urinary tract infection, Uropathogens, Sultan Qaboos University Hospital, Oman